Effects of thermal history on temperature-dependent flight performance in insects : Ceratitis capitata (Diptera: Tephritidae) as a model organism - Esterhuizen, Nanike (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.